The effect of inhaled frusemide on airway sensitivity to inhaled 4.5% sodium chloride aerosol in asthmatic subjects. Issue 3 (March 1993) - Rodwell, L T; Anderson, S D; du Toit, J I; Seale, J P
Abstract : BACKGROUND: Frusemide inhaled by asthmatic subjects before a variety of indirect bronchial challenges inhibits the airway response to these challenges. Since inhalation of hyperosmolar saline is an indirect bronchial challenge, the effect of inhaled frusemide and its vehicle on airway sensitivity to a 4.5% sodium chloride (NaCl) aerosol challenge was investigated. METHODS: Eleven asthmatic subjects (five females, six males) who had a 20% fall in forced expiratory volume in one second after 4.5% NaCl challenge were enrolled in this double blind controlled crossover trial. Sensitivity was measured as the dose of aerosol required to provoke a 20% fall in FEV1. Frusemide (33.2 mg) or its vehicle was delivered through a Fisoneb ultrasonic nebuliser and inhaled 10 minutes before challenge with 4.5% NaCl. A Mistogen ultrasonic nebuliser was used to generate the 4.5% NaCl aerosol and FEV1 was measured before and one minute after each challenge period of 0.5, one, two, four, eight, eight and eight minutes. The doubling dose difference for PD20 was calculated. RESULTS: Frusemide or vehicle had no effect on baseline lung function. The geometric mean PD20 after vehicle was 1.3 ml with a 95% confidence interval of 0.7-2.3 and after frusemide was 8.2 ml with a 95% confidence interval of 4.7-14.1. This represented a 2.6 doubling dose increase in PD20 after frusemide inhalation. In five of the 11 subjects an increase from baseline FEV1 occurred after exposure to 4.5% NaCl challenge in the presence of frusemide. This transient bronchodilatation may be caused by the release of prostaglandin E2. CONCLUSION: Inhalation of frusemide is very effective in delaying airway narrowing induced by an aerosol of 4.5% NaCl in asthmatic subjects.